2014
DOI: 10.3109/14767058.2014.923395
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preterm neonates with patent ductus arteriosus (PDA): intestinal blood flow characteristics and clinical outcomes

Abstract: ELBW preterm neonates with large PDA may have attenuated intestinal blood flow responses to feedings. There was also an association with higher rates of necrotizing enterocolitis and feeding intolerance in the large PDA group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 27 publications
1
37
0
1
Order By: Relevance
“…This could be ascribed to the small amount of enteral feeds these infants received in proportion to total fluids as well as the small sample size. The effect of PDA and ductal steel on the SMA blood flow is well recognized; 30,31 since almost all infants in this study had PDA, we were not able to analyze the bearing of PDA on the SMA blood flow velocities.…”
Section: Discussionmentioning
confidence: 90%
“…This could be ascribed to the small amount of enteral feeds these infants received in proportion to total fluids as well as the small sample size. The effect of PDA and ductal steel on the SMA blood flow is well recognized; 30,31 since almost all infants in this study had PDA, we were not able to analyze the bearing of PDA on the SMA blood flow velocities.…”
Section: Discussionmentioning
confidence: 90%
“…A similar trial was performed in extremely low birth weight infants by Havranek et al in 2015 [57]. Pre-and post-prandial time-averaged mean, peak-systolic, and end-diastolic velocity in SMA were measured in preterm infants aged 5-7 days.…”
Section: Impact On Hemodynamics Response To Feedsmentioning
confidence: 97%
“…Similarly, this group showed reduced SrSO 2 and SCOR patterns before and after feeding administration, but the between-group comparison did not reach statistical significance at any time point. The small study sample of these trials [57,59], however, may have limited the power of the study analysis and the observed non-significant results.…”
Section: Impact On Hemodynamics Response To Feedsmentioning
confidence: 99%
See 1 more Smart Citation
“…(45)(46)(47) The effects of a hemodynamically significant PDA on superior mesenteric artery (SMA) blood flow have been examined, with some correlation seen in Doppler blood flow velocity parameters. (47)(48) SMA blood flow response has been noted to be blunted in the presence of a PDA in baboons and human infants (49)(50). …”
mentioning
confidence: 97%